Bright Yb3+ complexes for efficient pure near-infrared OLEDs. (November 2021) - Metlin, Mikhail T.; Goryachii, Dmitry O.; Aminev, Denis F.; Datskevich, Nikolay P.; Korshunov, Vladislav M.; Metlina, Daria A.; Pavlov, Alexander A.; Mikhalchenko, Lyudmila V.; Kiskin, Mikhail A.; Garaeva, Veronika V.; Taydakov, Ilya V.
Abstract: A series of neutral Yb 3+ and Gd 3+ complexes with isomeric 4, 4, 4-trifluoro-1-(naphthalenyl)butane-1, 3-diones and 1, 10-phenanthroline as an ancillary ligand were synthesized and characterized by a full range of analytical methods, including elemental analysis, FTIR and NMR spectroscopy, single crystal X-ray analysis, cyclic voltammetry (CVA) and thermal analysis (TG/DTA). Moreover, the unexpected formation of a mixed diketonate-carboxylate Yb 3+ complex [Yb(2-Naph)2 (CF3 COO)(phen)(H2 O)] from [Yb(2-Naph)3 (phen)] in solution was observed. The photoluminescence quantum yield (PLQY) for complex [Yb(2-Naph)3 (phen)] in the near infra-red region (one band with a peak at 980 nm) was about 3, 2%. This value is close to the highest one reported for 1, 3-diketonate complexes of Yb 3+ ion to date. The energy transfer process is discussed in details, based on the results of TD-DFT calculations and experimental photophysical measurements. These complexes were successfully used as emitters in multilayer OLEDs. The electroluminescence quantum efficiency corresponding to the sole band at 980 nm reached 0.042% with a maximum irradiance of 11 μ W/cm 2 at 8.5 V for [Yb(2-Naph)3 (phen)] based device, which is unusually high for such type of emitters. Highlights: Novel Yb 3+ complexes with isomeric naphthalene-based fluorinated 1, 3-diketones were synthesized. Photoluminescence quantum yield for one of complexes reached 3.2%. A multilayer mixed-processed OLEDs based on new Yb 3+ compounds were designed. Designed OLEDs have high electroluminescent quantum yield up to 0.042% at 980 nm.